The Effect of Variations of Hydrothermal Temperatures on Ex-Situ Hydroxyapatite/Al2O3 Doping Process from Papai Shrimp (Acetes erythraeus) - Bemis, Restina; Puspitasari, Ratih Dyah; Heriyanti, Heriyanti; Rahmi, Rahmi; Priyanti, Gessy Tri (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Hydroxyapatite (HA) is an alloplastic material that is commonly used as a substitute for bone grafts or bone grafts because it has bioactive properties, namely osteoconduction. This study aims to improve or develop the function of hydroxyapatite to become a strong and resilient biological device that can withstand loads for appropriate functions such as bone implants. Therefore, it is necessary to modify the structure, among others, by the reinforcement process (composite formation) with other materials.The doping of hydroxyapatite/Al2O3 in this study was carried out using the hydrothermal method. The hydrothermal method is one of the hydroxyapatite synthesis methods carried out at high pressure and temperature to achieve equilibrium. The material used in this study was papai shrimp as a source of calcium. The temperature has an effect in this study where the higher the doping temperature used, the higher the degree of crystallinity, particle size homogeneity, and porosity value. From the doping results, it is known that a temperature of 300Â°C produces a degree of crystallinity of 54.32% and a crystal size of 3.75 nm with a porosity value of 99.38%. This result is much better than the undoped hydroxyapatite in the previous study.